E-FANGELSIM OF TURKISH FOOTBALL SUPPORTERS - YAŞAR, Onur Mutlu; TURĞUT, Murat (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
It is seen that there are many studies in the literature on subjects such as loyalty and fanaticism for sports fans. The concept of e-angelism was adapted and evaluated by Dwyer, et al. from a different perspective. According to this point of view, it is stated that sports fans who have high level of identification and adherence to their favorite teams have spread and advertised their own teams as EFanjelism. Evaluations, it was determined that the level of E-Fangelism of the supporters of football teams and the differences according to the different variables (Age, Income, Status, Education, Favorite Team) are the main objectives of the study. The tudy involved a quantitative research methodology and convenience sampling with a total sample of 1752 sports fan. Sports Team Efangelism Scale consisting of 12 items and 4 sub-dimensions which were developed by Dwyer, Greenhalgh et al. and adapted to Turkish by Yüksekbilgili) were used. According to results of ANOVA and t-tests, it is found out that there were significant differences between some demographic variables of football fans in different dimensions.